2011
DOI: 10.1177/0363546510392012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complications After Minimally Invasive Surgical Repair of Acute Achilles Tendon Ruptures

Abstract: Long-term outcome after minimally invasive Achilles tendon rupture repair is excellent. Rerupture and severe wound infection are the most important complications with lasting negative effect on outcome. It justifies the use of rerupture as a relevant outcome measure in treatment evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 15 publications
1
42
1
Order By: Relevance
“…This variability may be due to any number of factors – gender, method of management, plyometric strength deficits, psychological components, and other physical changes indirectly related to injury and recovery course[4,2325]. Patients may be physically able to return to sports activities[26], but the fear of re-rupture may cause an individual to avoid the sports activity during which injury occurred[14]. Patients may also develop additional musculoskeletal problems related to changes in gait biomechanics[2729] such as knee injury or contra-lateral Achilles tendinopathy (25%) and rupture (6%)[30].…”
Section: Introductionmentioning
confidence: 99%
“…This variability may be due to any number of factors – gender, method of management, plyometric strength deficits, psychological components, and other physical changes indirectly related to injury and recovery course[4,2325]. Patients may be physically able to return to sports activities[26], but the fear of re-rupture may cause an individual to avoid the sports activity during which injury occurred[14]. Patients may also develop additional musculoskeletal problems related to changes in gait biomechanics[2729] such as knee injury or contra-lateral Achilles tendinopathy (25%) and rupture (6%)[30].…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Recent studies have found that long-term outcome after minimally invasive Achilles tendon rupture repair is excellent, with a low rate of complications. [26,27] We believe our minimally invasive percutaneous suturing conforms to the anatomical physiological feature of the Achilles tendon and meets the healing requirements inside the tendon. In particular, the technique has the following advantages:…”
Section: Discussionmentioning
confidence: 82%
“…Many surgical and conservative treatments for patients with Achilles tendon injuries have been studied (21)(22)(23). Several investigators have compared minimally invasive or Henr ıquez et al (24) found that function did not differ markedly between patients who had undergone minimally invasive or open surgery.…”
Section: Discussionmentioning
confidence: 99%